Internalizing Change Capacity in Secondary Schools Through Organizational Change - Hannay, Lynne M.; Ross, John A. (Alberta Journal of Educational Research, 2001)
In this article we focus on understanding the meaning of change capacity in secondary schools. Our definition of change capacity focuses on organizational dimensions. We review evidence from a longitudinal study of change in nine secondary schools in a single district to argue that change capacity consists of three attributes: liberation from structures that inhibit innovation (in our case breaking the mold of subject department organizational structures), honoring dissonance, and forging new relationships. We identify the conditions that contribute to the development of change capacity in secondary schools by examining the contributors to the emergence of each element.